2020
DOI: 10.14507/epaa.28.5235
|View full text |Cite
|
Sign up to set email alerts
|

Muddy sensemaking: Making sense of socio-emotional skills amidst a vague policy context

Abstract: Education laws and policies have moved toward promoting socio-emotional (SEL) skills, adopting numerous terminologies in their standards. However, the incremental change has left compensatory education practitioners who are committed to promoting SEL opportunities with little guidance when the programs’ governing policies do not include language acknowledging the importance of SEL to student success. Additionally, the ongoing debate in the SEL field about which taxonomies might best capture the skills and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…An equity-oriented lens is however acutely important given the continued indignation of racial disparities in the United States. Research conducted by Muñiz (2020), illustrated the importance of cultural capital and the role of trauma in relation to the five core competencies. Additionally, their research supported previously identified issues such as lack of clarity for practitioners to promote the five core competencies when faced with issues of race or trauma.…”
Section: Casel Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…An equity-oriented lens is however acutely important given the continued indignation of racial disparities in the United States. Research conducted by Muñiz (2020), illustrated the importance of cultural capital and the role of trauma in relation to the five core competencies. Additionally, their research supported previously identified issues such as lack of clarity for practitioners to promote the five core competencies when faced with issues of race or trauma.…”
Section: Casel Frameworkmentioning
confidence: 99%
“…Educators have started to thoroughly examine the benefits of SEL, including its impact on academics, behavior, and potential contributions to our society and economy (Belfield et al, 2015; CASEL, 2019a; Durlak et al, 2017; Jennings & Frank, 2017; Jennings & Greenberg, 2009; Mahfouz et al, 2019; Mart et al, 2017; Muñiz, 2020; Patti et al, 2017; Schonert-Reichl, Hanson-Peterson, et al, 2017). Federal and state government involvement with SEL implementation began with recognition of the financial value of comprehensive programming in addition to academics.…”
Section: Casel Frameworkmentioning
confidence: 99%
“…Studies focused on educational actors are still emergent (see Collie et al, 2011;Muñiz, 2020;Sorondo, 2023), seeking to analyze internal school factors crucial to the successful implementation of SEL programs. Some of these studies highlight the importance of commitment to SEL (see Collie et al, 2015;Nielsen et al, 2019) and the training provided to professionals (see Esen-Aygun and Sahin-Taskin, 2017; Barnes and McCallops, 2019) as factors leading to adequate SEL program implementation.…”
Section: Introductionmentioning
confidence: 99%